ANALISIS PROGRAM SMASHED SEBAGAI AKTIVITAS CSR PT. DAPOER DONGENG NOESANTARA DALAM MEMPERTAHANKAN CITRA POSITIF - Annisa Putri Amalia, (2023)
This study aims to analyze the activities carried out by PT. Dapoer Dongeng Noesantara through the SMASHED Program in social activities to help help children, youth and families in Indonesia master life skills and cultural skills. This study uses a qualitative research method that is qualitative descriptive. The theory used in this research is Legitimacy Theory. The data collected in this study consisted of primary data (interviews, documentation and literature study) and secondary data (literature study and results of previous research). From this study, researchers sought information from several informants related to the activities carried out by the company using Penta Helix Analysis. Researchers also use SWOT analysis to be able to measure the strengths and weaknesses of the resources owned by the company as well as the opportunities and challenges faced by the company. The data analysis technique used in this study is the technique of data collection, data reduction, presentation of data conclusions and data verification. The results of the research show that the CSR activities carried out by PT. Dapoer Dongeng Noesantara through the SMASHED program basically has influence and plays an active role in enhancing the company's image, reputation and credibility. In this case, what must be done by PT. Dapoer Dongeng Noesantara is considering expanding the scope of beneficiaries from the SMASHED CSR program, so that it is not just junior high school-age youth, but to all levels of education.